MAS Integration and Controllership Effectiveness: Evidence of a Preparer-User Perception Gap - Barbara E. Weißenberger; Hendrik Angelkort; Gero Holthoff (BuR - Business Research, 2012)
Recent evidence suggests that managers establish a positive link between management accounting system (MAS) integration and controllership effectiveness, which is fully mediated by the perceived consistency of financial language. Our paper extends this research by analyzing whether controllers have similar perceptions on MAS design. Testing a series of multi-group structural equation models, we find evidence for a preparer-user perception gap with respect to the mediating impact of a consistent financial language. Our results contribute to the still-ongoing controversial debate on MAS integration by indicating that the effectiveness of MAS design cannot be evaluated solely from an instrumental perspective independent from users perceptions
urn:nbn:de:0009-20-35038
Keywords: 650; managerial accounting; controllership effectiveness; preparer-user perception gap; structural equation modeling (SEM); survey; multi-group analysis; Management-Informationssystem; Controlling-Informationssystem; Strukturgleichungsmodell; Operations Research; Deutschsprachiger Raum